A distributed knowledge management infrastructure based on a Topic Map grid. (8th June 2009) - Korthaus, Axel; Aleksy, Markus; Henke, Stefan
Modern enterprise knowledge management systems typically require distributed approaches and the integration of numerous heterogeneous sources of information. A powerful foundation for these tasks can be Topic Maps, which not only provide a semantic net-like knowledge representation means and the possibility to use ontologies for modelling knowledge structures, but also offer concepts to link these knowledge structures with unstructured data stored in files, external documents etc. In this paper, we present the architecture and prototypical implementation of a Topic Map application infrastructure, the 'Topic Grid', which enables transparent, node-spanning access to different Topic Maps distributed in a network.